2006
DOI: 10.1521/jscp.2006.25.10.1059
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Forgiveness Process Models and A Coping Framework to Guide Future Research

Abstract: Despite substantial advances in other areas of forgiveness research, empirical evaluation of a fundamental aspect of forgiveness, the process itself, has been virtually nonexistent. This article reviews the existing literature and concludes that although numerous process models have been proposed, many lack a coherent theoretical grounding, and few have been empirically validated. Importantly, understanding of the forgiveness process is hindered by a lack of consensus on what forgiveness is, and consequently w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
1
29

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(168 citation statements)
references
References 66 publications
(130 reference statements)
4
134
1
29
Order By: Relevance
“…On the other hand, forgiveness is often seen as an affective coping mechanism (Worthington & Scherer, 2004) and is closely associated with mental health, physical well-being and positive affect . Some researchers insistently emphasize forgiveness process in terms of coping (Pargament & Rye, 1998;Strelan & Covic, 2006;Worthington & Scherer, 2004). For instance, Strelan and Wojtsiak (2009) found that individuals use similar coping strategies for both general stressors and interpersonal hurt.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, forgiveness is often seen as an affective coping mechanism (Worthington & Scherer, 2004) and is closely associated with mental health, physical well-being and positive affect . Some researchers insistently emphasize forgiveness process in terms of coping (Pargament & Rye, 1998;Strelan & Covic, 2006;Worthington & Scherer, 2004). For instance, Strelan and Wojtsiak (2009) found that individuals use similar coping strategies for both general stressors and interpersonal hurt.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, el perd贸n es un constructo que no est谩 exento de pol茅mica en relaci贸n a diferentes aspectos como su definici贸n, el supuesto beneficio para la persona que perdona, si debe implicar o no reconciliaci贸n con el ofensor qu茅 modelos te贸ricos pueden explicarlo (Guzm谩n, 2010;Prieto-Urs煤a, Carrasco, Cagigal, Gismero, Mart铆nez y Mu帽oz, 2012;Strelan y Covic, 2006).…”
Section: Antecedentesunclassified
“…Self-forgiveness is where the individual is the offender who knows they have misbehaved and try to accept it. In other words, self-forgiveness is when the individual stops blaming themselves for their mistakes (Strelan & Covic, 2006). Research has found that individuals tend to make harsher judgements about themselves than others (Maltby et al, 2001).…”
Section: Forgiveness Of Self and Othersmentioning
confidence: 99%